Poder Régio e Cortes em Portugal (Sécs. XII-XVI) - Cunha, Cristina (2021)
Throughout the Middle Ages there was a gradual strengthening of institutions of a more centralist nature (as in the case of the Monarchies and the Church), a phenomenon which was detected from the middle 11th century and developed at different rates in the various kingdoms. The thematic dossier aims to be part of the historiography dedicated to the Royal Power, in its various expressions and extensions. The present text includes a brief presentation of studies that aim to contribute to a better understanding of the history of power(s) in Portugal.